DISSOLUTION PROFILE STUDY FOR INNOVATION ANTI-RETROVIRAL DRUG PRODUCT NIKAVIR® AND ITS FIXED COMBINATION WITH LAMIVUDINE (PHOSPHALADINE®) - I. E. Shohin; Yu. V. Medvedev; T. N. Komarov; O. V. Klimova; B. V. Brovchenko (Разработка и регистрация лекарственных средств, 2019)
Biopharmaceutical solubility was experimentally determined for innovation anti-retroviral API phosphazide (Nikavir®) which was classified as BCS Class 3 drug. Dissolution profile test for Nikavir® 200 mg and 400 mg in three media pH 1.2, 4.5, 6.8 was conducted, and equivalence for both dosages was shown. Also dissolution profile test for phosphazide and lamivudine fixed combination 150 mg + 400 mg (Phosphaladine®) was performed in three media pH 1.2, 4.5, 6.8 against two reference drug products Nikavir® 400 mg and Epivir® (lamivudine) 150 mg. Dissolution profiles for lamivudine were equivalent in all three media, and phosphazide profiles were equivalent in pH 1.2. Studied batch of phosphazide and lamivudine fixed combination was recommended to be a clinical biobatch for further BE studies.